2014
DOI: 10.1016/j.jval.2014.08.303
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Pharmacoeconomics Studies of Treatment for Major Depressive Disorder in China

Abstract: A 7 1 9 -A 8 1 3 A769 more than one worker over four will spend one hour per day providing care to a patient with dementia. Increasing the proportion of treated patients may be a way to control costs and reduce burden on the society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Few economic studies using modeling techniques have been developed in China [32,51], and recent CE studies for depression and Parkinson's disease in China have shown that most studies published correspond to economic analyses 'piggybacked' on clinical studies where the clinical endpoints are loosely defined, and the costs are often restricted to cost of drugs only [52,53]. This can be explained by the difficult to document patient paths, burden of illness and difficulty in identifying unit costs for resource utilization in China, all of which this present study aimed to overcome.…”
Section: Discussionmentioning
confidence: 99%
“…Few economic studies using modeling techniques have been developed in China [32,51], and recent CE studies for depression and Parkinson's disease in China have shown that most studies published correspond to economic analyses 'piggybacked' on clinical studies where the clinical endpoints are loosely defined, and the costs are often restricted to cost of drugs only [52,53]. This can be explained by the difficult to document patient paths, burden of illness and difficulty in identifying unit costs for resource utilization in China, all of which this present study aimed to overcome.…”
Section: Discussionmentioning
confidence: 99%